Distal clavicle fractures in children - Pedro José Labronici; Ricardo Rodrigues da Silva Junior; Marcos Vinícius Viana Franco; Gustavo José Labronici; Robinson Esteves Santos Pires; José Sergio Franco (Revista Brasileira de Ortopedia, 2016)
ABSTRACT OBJECTIVE: To analyze fractures of the distal clavicle region in pediatric patients. METHODS: Ten patients between the ages of five to eleven years (mean of 7.3 years) were observed. Nine patients were treated conservatively and one surgically. All the fractures were classified using the Nenopoulos classification system. RESULTS: All the fractures consolidated without complications. Conservative treatment was used for nine patients, of whom three were in group IIIB, three IIb, two IIa and one IV. The only patient who was treated surgically was a female patient of eleven years of age with a group IV fracture. CONCLUSION: The treatment indication for distal fractures of the clavicle in children should be based on the patient's age and the displacement of the fragments.